2021
DOI: 10.1126/sciadv.abc7609
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-induced eosinophils improve cytotoxic T lymphocyte recruitment and response to immunotherapy

Abstract: The efficacy of cancer immunotherapy is dictated by CD8+ T cell infiltration and the nature of the tumor microenvironment (TME). By inflaming the TME to favor CD8+ T cell immunity, radiation is now widely considered as a neoadjuvant for immunomodulation. Here, we observed that local irradiation enhances the infiltration of intratumoral eosinophils, and depletion of eosinophil dampens CD8+ T cell infiltration and diminishes the anti-tumor effectiveness of radiation. Retrospectively, we identified a strong corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 59 publications
1
28
0
Order By: Relevance
“…More recently, Cheng et al reported that eosinophil-related markers are substantially increased in the TME following radiation exposure. Using mouse models, they showed that eosinophil infiltration into the TME was also markedly increased after radiation [ 28 ]. Furthermore, they showed that increased eosinophils were not only associated with recruitment of CD8+ T-lymphocytes into the TME, but also that eosinophils were necessary for the cytotoxic anti-tumor response observed.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Cheng et al reported that eosinophil-related markers are substantially increased in the TME following radiation exposure. Using mouse models, they showed that eosinophil infiltration into the TME was also markedly increased after radiation [ 28 ]. Furthermore, they showed that increased eosinophils were not only associated with recruitment of CD8+ T-lymphocytes into the TME, but also that eosinophils were necessary for the cytotoxic anti-tumor response observed.…”
Section: Discussionmentioning
confidence: 99%
“…Eosinophil depletion attenuates CD8+ T cell infiltration and decreases the efficacy of radiotherapy. In addition, stimulation of eosinophils by the administration of IL-5 increases CAR-T cell infiltration and supports the abscopal effect [ 43 ].…”
Section: Eosinophils and Cancermentioning
confidence: 92%
“…In fact, reductions in MDSC frequency and function have been demonstrated during regular anti-tumor therapies, including chemotherapy, targeted therapy, immunotherapy, and combined therapy. However, other studies and our previous studies have shown that radiotherapy could induce an increase in MDSCs in the TME and spleen ( van Meir et al, 2017 ; Cheng et al, 2021 ). Regarding chemotherapeutic agents, 5-fluorouracil (5-FU), gemcitabine, and pemetrexed could decrease MDSC accumulation in various cancers.…”
Section: Strategies Targeting Mdscs For Optimizing Cancer Treatmentmentioning
confidence: 62%